2021
DOI: 10.3390/cancers13153894
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Immunohistochemical Study of the SWI/SNF Complex Expression Status in Gastric Cancer Reveals an Adverse Prognosis of SWI/SNF Deficiency in Genomically Stable Gastric Carcinomas

Abstract: The SWI/SNF complex has important functions in the mobilization of nucleosomes and consequently influences gene expression. Numerous studies have demonstrated that mutations or deficiency of one or more subunits can have an oncogenic effect and influence the development, progression, and eventual therapy resistance of tumor diseases. Genes encoding subunits of the SWI/SNF complex are mutated in approximately 20% of all human tumors. This study aimed to investigate the frequency, association with clinicopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
1
7
2
Order By: Relevance
“…Some studies on gastric adenocarcinoma found SWI/SNF complex abnormalities to be an independent prognostic factor for OS in the GS subtype 28,29 . Interestingly, ARID1A negative expression exhibited worse survival in the EBV subtype, 29 which was inconsistent with our present study, possibly due to different ARID1A classification methods or bias caused by too few patients in the subgroup.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies on gastric adenocarcinoma found SWI/SNF complex abnormalities to be an independent prognostic factor for OS in the GS subtype 28,29 . Interestingly, ARID1A negative expression exhibited worse survival in the EBV subtype, 29 which was inconsistent with our present study, possibly due to different ARID1A classification methods or bias caused by too few patients in the subgroup.…”
Section: Discussioncontrasting
confidence: 99%
“…highest loss ratio (12/21, 57.14%), followed by ARID1A (5/21, 23.81%) and SMARCA4 (3/21, 14.29%). The loss ratio of the above three subunits in undifferentiated/ dedifferentiated gastric carcinoma was significantly higher than that in ordinary gastric adenocarcinoma [8,9], suggesting a correlation between the differentiation status and the loss of SWI/SNF complex subunits. Our current study also showed the CSC phenotype appeared more frequently in the SWI/SNF complex deficient group (Table 4).…”
Section: Discussionmentioning
confidence: 89%
“…Many studies on the loss of SWI/SNF complex subunits in conventional gastric adenocarcinoma have been reported [8,9]. Conversely, in undifferentiated/dedifferentiated gastric carcinoma, studies related to SWI/SNF complex are limited due to the rarity of cases.…”
Section: Introductionmentioning
confidence: 99%
“…This can be accomplished via an increase in the accessibility to transcription factors, as the SWI/SNF complex has the ability to mobilize and shift nucleosomes 59,60 . Multiple subunits of the SWI/SNF complex have been associated with gastric cancer development [61][62][63][64] . Most notably, unbiased genome and exome sequencing studies have identified ARID1A, a gene encoding the DNA interacting subunit of the SWI/SNF complex 65 , as the second most frequently mutated gene after TP53 in GC 5,66,67 .…”
Section: Alterations In Chromatin Remodeling Complexes Play Functiona...mentioning
confidence: 99%